Technological and Economic Challenges of Green Hydrogen Production in Morocco for the European Market - Bacaoui Mostafa; Marwan Houssain; Jazouli Taleb (Lamintang Education and Training (LET) Centre, 2025)
This study explores Morocco’s potential as a green hydrogen producer, focusing on its capacity to serve the European market. As the world shifts to sustainable energy, Morocco, with its abundant renewable energy resources, particularly solar and wind, is positioned to play a significant role in green hydrogen production. The study aims to assess Morocco’s potential for large-scale hydrogen production, its economic and environmental benefits, implementation challenges, and export opportunities to Europe. A descriptive qualitative methodology was used, using a case study analysis of Morocco’s energy policies, infrastructure, and potential. Data were collected through document analysis and semi-structured interviews with energy experts and policymakers. The study findings reveal that Morocco’s strategic location, coupled with its renewable energy resources, make it an ideal candidate for green hydrogen production. However, technical challenges, such as inefficient electrolysis technology, and logistical issues associated with infrastructure development pose significant barriers. Despite these challenges, Morocco’s growing role in the global green hydrogen market presents substantial economic benefits, including job creation and emission reductions. Future research should address specific technological barriers, including storage and transportation solutions, and further explore financial models to support large-scale green hydrogen projects. In addition, future research should investigate the regulatory framework needed to position Morocco as a competitive player in the global hydrogen market.